Kombucha: Challenges for Health and Mental Health - Patrícia Batista; Maria Rodrigues Penas; Catarina Vila-Real; Manuela Pintado; Patrícia Oliveira-Silva (Foods, 2023)
Background: Increasing research into probiotics is showing potential benefits for health in general and mental health in particular. Kombucha is a recent beverage and can be considered a probiotic drink, but little is known about its effects on physical and mental health. This product is experiencing growth in the market; however, there are no scientific results to support its potential for physical and mental health. Aim: This review article aims to draw attention to this issue and to highlight the lack of studies in this area. Key findings and conclusions: The lack of legislation for the correct marketing of this product may also constrain clinical studies. However, clinical studies are of utmost importance for an in-depth understanding of the effects of this product on the human body. More research is needed, not only to better understand the impact of Kombucha on the human body, but also to ensure the application of regulatory guidelines for its production and marketing and enable its safe and effective consumption.